Pengaruh Job Enrichment dalam Peningkatan Keterlibatan Kerja Pekerja - , Febriditya Atgung Nugroho, S.Psi, Drs. Fathul Himam, MPSi., MA., Ph.D., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Job design is a system which considered as the vital aspect to increase employeeâs internal motivation and finally their job involvement. Direct Contract Employee is an employment type from company, whose workload is only about routine responsibility. Therefore it needs a basic system to improve their involvement, such as defining working behavior indicators from core competency. This job is also part of Job Redesign Process, especially in component Skill Variety. The aim for this experimental study is to increase job involvement from direct contract employee by using Job Enlargement as a part of Job Enrichment process. The subject of this experimental study is direct contract employees with amount 44 workers. They will be divided into 2 main groups, one is a control group and the other is an experimental group. This experimental study will use Randomized Control Group PreTest-PostTest Design and analysis method with T test. The Result is that there is difference between experiment group and control group that indicates an influence to employeeâs job involvement. Keywords : Job Design, Job Involvement, Internal Motivation, Job Enrichment, job Enlargement, Competency, Working Behavior Indicators.